Odškodninska odgovornost internetnih posrednikov - Damjan, Matija (Pravni letopis, 2010)
The content available on the Internet may violate various legal norms (e.g. intellectual property rights and personal rights) and thereby cause damage. Internet service providers and other Internet intermediaries, due to their technical role in the transmission and storage of information have a certain degree of control over third parties content. The key question is when and to what extent should such intermediaries bear responsibility for the damage, and to what extent should the liability lie with the original content providers. The reasons for and against Internet intermediary liability are discussed in the article. Presented are the general rules of European and Slovenian law on intermediary liability, which distinguish between three types of information society services: mere conduit, caching and hosting. Certain outstanding issues are discussed concerning the required speed of action, the validation of a takedown notice, the hyperlink liability and the new challenges posed by the Web 2.0.
Keywords: avtorske pravice; internet; kršenje; odškodninska odgovornost; ponudba; privacy; storitve; zasebnost